Melting stones - Pierce, Tamora (New York : Scholastic Press, 2008)
Residents of the island of Starns send for help from Winding Circle temple, and when prickly green mage Rosethorn and young stone mage trainee Evvy respond, Evvy finds that the problem is with a long-dormant volcano and tries to use her talents to avert the looming destruction.
"This work was originally published as an audio book by Full Cast Audio in 2007"--T.p. verso.
Keywords: Magic -- Fiction; Fantasy